UNVEILING THE POTENTIAL OF OXADIAZOLE TRIAZINE NUCLEOSIDE DERIVATIVE AS AN INHIBITOR OF SARS COV-2: A COMPUTATIONAL BREAKTHROUGH - Sudan, Madhu; Arora, Sarika; Yadav, Danveer Singh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
SARS-CoV-2 created havoc worldwide in 2019 and was responsible for many deaths. No antiviral drugs have been developed to combat this virus. Oxadiazoles have multiple biological functions, such as anti-inflammatory, anti-tussive, anticancer, analgesic, cough suppressant, anti-oxidant, vasodilator, and more. Many drugs with oxadiazole nuclei have been repurposed to combat COVID-19. To identify a potent oxadiazole derivative against SARS-CoV-2, this article screened 45 substituted oxadiazole triazine nucleoside analogs to counter the three key targets of the SARS-CoV-2 life cycle: spike protein, main proteases, and RNA-dependent RNA-polymerase. The geometry of 45 substituted oxadiazole triazine nucleoside analogs was optimized by density functional theory (DFT) with the B3LYp method. Drug-likeness criteria, ADMET prediction, and docking were carried out for screening. Further analysis of ligand-protein interactions was performed by molecular dynamics simulation at 50 ns. Compounds 1a (-8.5 kcal) and 1m (-8.5 kcal) showed an excellent binding affinity with main proteases (6LU7) and -7.8Kcal, -7.6Kcal, respectively, for RdRp (6M71), while compound 1a and 1m exhibited -8.0 kcal, -8.2 kcal binding affinity respectively for spike protein (6LZG). The MD simulation of the protein-ligand complex with compounds 1a and 1m exhibited good compactness and stability, further validating the docking results. This study proposes these two compounds would be robust inhibitors of SARS CoV-2.